HUBUNGAN DUKUNGAN KELUARGA DENGAN KUNJUNGAN LANSIA KE POSYANDU LANSIA DI POSYANDU BUGENVIL 50 DESA GUGUT KABUPATEN JEMBER - Nur Fadilah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2015)
One measure of the progress of a nation is often seen from the life expectancy of its inhabitants. Old age is a period of life span that is marked by changes or decline in bodily functions. The purpose of this study was to analyze the relationship between family support and elderly visits to the elderly Posyandu at Posyandu Bugenvil 50, Gugut Village, Jember Regency. This research is a correlation study (correlation study). The population in this study was the elderly in the Bugenvil 50 posyandu in Gugut Village, Jember Regency as many as 210 people. The number of samples was 68 people, the sampling used was simple random sampling. The results of this study indicate that family support is good as many as 39 people (57.4%), not good 29 people (42.6%), and the activeness of elderly visits to posyandu is as much as 38 people (55.9%), active 30 people (44.1%) . Based on the chi square test results obtained x2 count (11,257)> x2 table (3.48) with n p value (0.001) <a (0.05). This means that Ha was accepted, that is, there was a Relationship between Family Support and Elderly Visit to the Posyandu. The conclusion from this study is that there is a positive relationship between family support and elderly visits to the Posyandu of the elderly in Posyandu Bugenvil 50, Gugut Village, Jember Regency